Aquarius helicase facilitates HIV-1 integration into R-loop enriched genomic regions - Penzo, Carlotta; Özel, Ilayda; Martinovic, Moreno; Kuzman, Maja; Glavas, Dunja; Stanić, Mia; Reichenbach, Thomas; Müller, Thorsten G.; Rheinberger, Mona; Godarzi, Negar; Lapaillerie, Delphine; Srezovic, Bruno; et al. (Nature microbiology, 2025)
HIV-1 integration into host chromosomes, essential for viral replication, is catalysed by viral integrase (IN). IN recurrently targets intronic regions of transcriptionally active genes, but a detailed understanding of this process is still unclear. Here, using ex vivo activated human primary CD4+T cells, we find that genomic RNA:DNA hybrids (R-loops) preferentially map to intronic regions of active genes that are typical HIV-1 integration sites. IN binds R-loops and their resolution enhances viral integration in vitro. We identify Aquarius (AQR), the splicing RNA helicase of the pentameric intron binding complex (IBC), which associates with IN and show that its RNA:DNA helicase activity promotes integration into hybrid substrates in vitro. Knockout of AQR in primary CD4+ T cells impaired overall integration efficiency, while sequencing of remaining integrations mapped them to intergenic and R-loop distal regions. These findings may have important implications for HIV-1 latency and reactivation and may thus identify novel therapeutic targets.
Online veröffentlicht: 20. August 2025
Gesehen am 25.02.2026